Study of reinforced concrete circular column crack control and modifcation in P-M interaction diagram - Eswaran, R.; Sivakumar, S. (Journal of Structural Engineering, 2024)
This paper presents the study of design methods for checking of Reinforced Cement Concrete (RCC) circular columnscrack width control. The various case studies of design explain the importance of crack width control in addition todesign for limit state of collapse ie., strength requirements. In the beginning, this paper explains the cases for which thehigher area of reinforcement is required for crack width control than the requirement for strength aspect. The sampledesign calculation for crack width checking is also presented. Next, this paper explains the safe zone in P-M interactioncurve as per SP-16 of Indian standards, where the circular sections are safe in both strength as well as crack widthcontrol requirements. The unsafe zone in P-M interaction curve describes the circular sections are safe as per strengthbut unsafe as per crack width control requirements. Finally the method for modification of P-M interaction curve inunsafe zone is explained by increasing the percentage of reinforcement to satisfy the crack width control. The modifieddesign charts for calculating area of reinforcement required are presented. These modified design charts provideguidance to the structural designer while designing for limit state of serviceability for RCC circular columns.